Memperkokoh Keharmonisan Umat Beragama Antara Konghucu dengan Umat Beragama Lain - Bernanda, Alfa Wena; Wakhudin, Wakhudin (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to elucidate initiatives fostering religious harmony, particularly among the Konghucu community and other religious groups in Indonesia—a diverse archipelagic nation with a myriad of ethnicities, religions, languages, customs, and beliefs. Embracing unity in diversity, the nation's individuals often prioritize ancestral traditions, language, and culture, shaping their perspectives on life. Despite these variations, the study underscores the nation's aspiration for perpetual unity. Utilizing a descriptive qualitative approach and discourse analysis methods, the research delves into Confucian values, focusing on religious tolerance. The process involves reviewing Konghucu scriptures, analyzing collected data, and systematically presenting enhanced research findings. The outcomes highlight continuous efforts to fortify unity and cohesion between the Konghucu community and other religious entities, emphasizing the universal teachings of love, peace, and tolerance inherent in all religions.